A polissemia e a representação espacial das preposições 'de' e 'para' do português brasileiro - Jeremias, Daiana do Amaral (2014)
This work employs Jackendoff’s localist approach (1983; 1992) to advance a proposal for a description of the polysemy of prepositions “from” and “to” in Brazilian Portuguese. According to our research, prepositions “from” and “to” can be considered polysemic items, given that each of these prepositions, individually, can attribute different meanings to its object of reference and these meanings can be cognitively related by a spatial-conceptual representation of trajectory. According to Ilari et al. (2008), the prepositions “from” and “to” occupy the origin and the final positions, respectively, in a spatial trajectory of the horizontal axis. However, the basic use of these prepositions, that is, the one in which we are able to interpret a meaning directly related to a physical space, can be extended to other meanings that can be conceptually interpreted as spatial. For a metaphoric interpretation of the imagetic scheme of the trajectory, Jackendoff (1983; 1992) proposes the Thematic Relation Hypothesis, according to which the spatial-conceptual spaces of prepositions can be explained through distinct semantic fields. This possibility of extension for spatial-conceptual meanings is based on the embodied experience of the speakers, because when we interpret conceptually a lexical item, we state that the real world furnishes us a substratum for our sensorial perceptions and for the conceptualizations that follow from it. Through this experience we unconsciously build structural experiences of meanings that are imagetic schemes, and metaphoric projections (JOHNSON, 1987). Thus, we hypothesize that the different meanings established by prepositions “from” and “to” can be related among themselves, that is, they have the same image scheme, corroborating the idea of a polysemy for these prepositions. We propose that through embodiment the speaker is able to extend cognitively the meaning of a lexical item to other conceptual meanings, that is, the basic spatial use of a preposition can be extended to metaphoric uses whose interpretation, of a spatial character, can be recovered through the semantic fields proposed by Jackendoff (1983; 1992). The semantic fields we shall deal with in this work are: Temporal, Possessional, Identificational, Circumstantial and Existential. Thus, we establish as the goals of our research as follows: a) to present the meaning relations established by prepositions “from” and “to”; b) to present the congnitive process of the embodied experience; c) to present the imagetic scheme of these two prepositions and d) the connection of non-spatial semantic fields, of the semantic relations of these propositions, within a localist approach. As our research methodology, we will analyze the semantic relations of Brazilian Portuguese sentences in which prepositions “from” and “to” establish meaning relationships, trying to identify, through the theory of the Thematic Relation Hypothesis, the relation of conceptual meanings, their respective semantic fields, with special base meanings.